A Convenient Split‐Intein Tag Method for the Purification of Tagless Target Proteins. (21st February 2018) - Cooper, Merideth A.; Taris, Joseph E.; Shi, Changhua; Wood, David W.
Abstract: In this work, we describe a novel self‐cleaving tag technology based on a highly modified split‐intein cleaving element. In this system, the N‐terminal segment of an engineered split intein is expressed in E. coli and covalently immobilized onto a capture resin, while the smaller C‐terminal intein segment is fused to the N‐terminus of the desired target protein. The tagged target can then be expressed in an appropriate expression system, without concern for premature intein cleaving. During the purification, strong association between the intein segments effectively captures the tagged target onto the capture resin while simultaneously generating a cleaving‐competent intein complex. Once the complex is purified by washing the column, intein‐mediated cleavage and release of the tagless target is induced with a simple shift in buffer pH from 8.5 to 6.2. The result is a convenient and effective method for the purification of traceless and tagless target proteins, which can be used in characterization and functional studies. © 2018 by John Wiley & Sons, Inc.